The Relationship Between Transformational Leadership Headmaster With Teacher Performance - Anwar Anwar; Yenni Agustina; Ahmad Yani; Abubakar Abubakar; Darmawati Darmawati (JURNAL SERAMBI ILMU, 2022)
This study aims to determine teacher performance, to determine the relationship between Principal Transformational Leadership and Teacher Performance, to determine the level of relationship between Principal Transformational Leadership and Teacher Performance at SMP Negeri 13 Banda Aceh. The method used in this research is descriptive quantitative. The population in this study were all teachers at SMP Negeri 13 Banda Aceh with a total of 28 teachers, while the sample used as respondents in this study were all teachers at SMP Negeri 13 Banda Aceh, amounting to 28 people. Data collection techniques are observation, documentation and questionnaires/questionnaires. While the Questionnaire/Questionnaire is in the form of a Likert scale. To analyze the data used product moment correlation formula. The results of this study indicate that: (1) teacher performance at SMP Negeri 13 Banda Aceh is very good, (2) There is a significant relationship between the principal's transformational leadership and teacher performance, this is in accordance with the results of the t test, which shows that tcount ttable (-6.467 -2.051), (3) The level of relationship between the principal's transformational leadership and teacher performance is quite strong.